Podcast of the Food Systems Transformation in Kenya book launch - Elouafi, Ismahane; Swinnen, Johan; Mueke, Hon. Jonathan; Obare, Gideon; Mbuthia, Juneweenex; Breisinger, Clemens; Ambuko, Jane; Keenan, Michael; Ngugi, Rose; Laibuni, Nancy; Chele, Anne; Djikeng, Appolinaire; et al. (International Food Policy Research Institute, 2024)
BOOK LAUNCH Food Systems Transformation in Kenya: Lessons from the Past and Policy Options for the Future Co-organized by IFPRI, International Livestock Research Institute (ILRI), Ministry of Agriculture and Livestock Development (MoALD), and CGIAR Initiative on National Policies and Strategies (NPS) JAN 8, 2024 - 4:30 TO 5:45PM EAT